Kinship, Marriage and Traces of Social Interaction - Aspects on the hunter-gatherer societies in northern Sweden during the Bronze Age and early Iron Age - Bolin, Hans (Current Swedish Archaeology, 1996)
A central problem in the explanation and description of decentralized hunter-gatherer societies is what kind of traces different sorts of social interaction will leave in the archaeological material. It is here suggested that the distribution of asbestos-tempered ceramic ware in northern Sweden during the Bronze Age and early Iron Age was a result of the social interaction between different groups. The decoration on the cermic ware is suggested to represent traces of intermarriage relations. It is further argued that the hunter-gatherer societies were open to interaction with other groups and individuals.